A tapered glass microcapillary processing system for focusing a MeV H+ ion beam - Somrit Unai (2018)
Several recent reports have indicated that a tapered glass capillary tube with a tip size on the order of micrometers has a focusing effect on transmitted ion beams. In relation to our particular area of interest, this could be a simple and cheap way to generate a focused ion beam for ion beam lithography and beam-in-air analysis and irradiation applications. Here, details of the method and the equipment used to produce a tapered glass microcapillary tube will be described. The equipment, which is simply called a "glass microcapillary puller", is made using an induction heater. This method ensures that the glass tube, which is inserted inside and along the central axis of the solenoid, is heated uniformly in all directions. The heating temperature is adjusted by a power control, with a maximum temperature of approximately 2,000°C. The pulling tension is varied over a wide range by using different weights. Application of the tapered glass microcapillary for 2 MeV H+ ion beam lithography is also demonstrated.